Optimizing Production Amounts to Obtain Maximum Profits from Sales of Basreng and Duosus "Shafa Snack" in Medan City - Harahap, Lokot Muda; Manik, Enjelia; Amalia, Delvi Dede; Sinaga, Mulyati Patresia; Panjaitan, Rona; Ardini, Sarah Fadhila; Kabeakan, Siat Putri (Economic: Journal Economic and Business, 2024)
Linear programming is one of the most widely used operations research techniques in practice and is known for being easy to understand. The method in solving linear progamming on “Shafa Snack” is the graph method. The purpose of solving this linear progamming is to optimize the amount of production in obtaining maximum profit with data collection techniques through literature, observation and interviews. The optimal solution is obtained, namely the maximum profit of Rp1,875,000, with the number of duosus to be purchased from agents of 70kg and the number of basreng of 80kg. The results showed that duosus “chocolate filling” to achieve maximum profit of Rp1,875,000, with the number of snacks to be purchased at a price of Rp30,000 and a selling price of Rp40,000 per kg, resulted in a profit of Rp10,000 per kg. While basreng “spicy orange leaf” is purchased at Rp50,000 and sold for Rp65,000 per kg, with a profit of Rp15,000 per kg.